Brain Abscess Due to Gemella haemolysans - Lee, Mi Ra (American Society for Microbiology, 2004)
We present a case of brain abscess due to Gemella haemolysans and Bacteroides species in a 60-year-old-immunocompetent man who underwent dental procedures. The patient completely recovered following intravenous therapy with ampicillin and metronidazole for 6 weeks.